2014
DOI: 10.1097/ta.0000000000000245
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a nationwide trauma network for the care of severely injured patients

Abstract: Epidemiologic study, level III. Therapeutic/care management study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 18 publications
1
17
0
2
Order By: Relevance
“…229 The description for this network included a statement that government policy had been put in place to monitor development, but no outputs have been identified. (b) Studies reporting data on activity within clinical networks for specific conditions such as stroke, 230,231 trauma, 232,233 primary or community care 234,235 and ST elevation myocardial infarction. 236 Most of these studies claimed that clinical networks had improved care by, for example, increasing numbers of patients admitted to specialist facilities, 230,232 receiving thrombolysis for stroke 231 and improving mortality from trauma, 233 but all of them reported current activity and had not made any assessment of differences in care compared with before the network became operational or, therefore, whether the network had improved care.…”
Section: Resultsmentioning
confidence: 99%
“…229 The description for this network included a statement that government policy had been put in place to monitor development, but no outputs have been identified. (b) Studies reporting data on activity within clinical networks for specific conditions such as stroke, 230,231 trauma, 232,233 primary or community care 234,235 and ST elevation myocardial infarction. 236 Most of these studies claimed that clinical networks had improved care by, for example, increasing numbers of patients admitted to specialist facilities, 230,232 receiving thrombolysis for stroke 231 and improving mortality from trauma, 233 but all of them reported current activity and had not made any assessment of differences in care compared with before the network became operational or, therefore, whether the network had improved care.…”
Section: Resultsmentioning
confidence: 99%
“…Hay escasos estudios en red como ocurre en otros campos de la medicina 15 . Son necesarios trabajos colaborativos para diseminar la investigación dentro de la práctica clínica.…”
Section: Peculiaridades De La Investigación En Traumaunclassified
“…Los programas de advanced trauma life support sistematizan y homogeneizan el tratamiento inicial, teniendo un impacto positivo en el resultado final; por esta razón, se requiere un alto nivel de adherencia a dichos programas para mejorar los resultados 15,26 .…”
Section: Sistemas De Atención Al Trauma Graveunclassified
“…15 Collaborative studies are needed to disseminate research within clinical practice. There are few networked trials, in contrast to the situation found in other areas of Medicine.…”
Section: Peculiarities Of Research In Traumamentioning
confidence: 99%
“…In the United States, the key element is the trauma center, defined by levels and subjected to periodic evaluation. 15,26 Periodic recertification is required, and external audits can be performed.…”
Section: Severe Trauma Care Systemsmentioning
confidence: 99%